Colecciones, arqueólogos, instituciones y yacimientos en la España de los siglos XVIII al XX - España-Chamorro, Sergio,; Arranz Santos, Rebeca,; Romero Molero, Alberto, (Archaeopress Publishing Ltd, 2018)
The history of archaeological research has only recently become a research topic of interest within Spain. These 11 papers, first presented at a congress in March 2016, address several aspects from different perspectives that collectively enrich the historiography of Spanish archaeological research.